Pag-ibig sa Tinubuang Lupa A content analysis of the recorded songs of inang Laya - Abraham, Rebecca Litafina Astarte Demetillo
"This is a descriptive study, utilizing content analysis as the method of research. It aimed to determine and discuss Philippine issues and realities articulated in the recorded songs of guitarist Karina Constantino-David and vocalist Becky Demetillo-Abraham, otherwise known as Inang Laya (Mother Freedom), the duo that holds the distinction of being the first ever alternative or social realist artists to be included in a mainstream recording company's roster of talents. The following were applied in this research: Qualitative analysis to study the lyrical themes of the sample according to the socio-economic, socio-cultural, socio-political and environmental conditions or contexts of the Philippine historical period they represent; and quantitative analysis through frequency distribution tables to present concise data. Some of the secondary sources for this study were written materials, ranging from books to unpublished undergraduate and graduate theses. On the other hand, included as primary sources were selected written materials, the author's personal interview with a UP Diliman Musoc Technology teacher regarding the production, manufacture, distribution and marketing of local and foreign music, the recording of a UP Diliman Filipino professor's lecture on songs and nationalism, and the recordings of Inang Laya's lecture-concerts. Two sets of instruments, a content analysis form and an interview guide/schedule, were imperative in gathering data from the other primary sources: the four Inang Laya cassettes and compact discs (CDs), and the two Inang Laya members themselves. The interviews for this study, David and Abraham, were chosen through the judgmental or purposive sampling technique while the sample songs embodied the complete population of songs in the collection. Although rendered in Euro-American popular music styles, Inang Laya's 55 recorded songs in three cassettes and one double cassette/CD are known in the Philippine music industry as alternative music, specifically because of their social realist lyrical content. The researcher divided Philippine history into five categories: The Revolt Against Spain with six sings, the American and Japanese Regimes with five, the First Quarter Stroem and Martial Law with 12, the Campaign Against the Dictatorship with 19, and the Challenges to the Present with 13 dongs, Human Rights with nine sub-themes totaling 14 songs, Women with seven sub-themes totaling 10 sings, and Social Justice with three sub-themes totaling eight songs. These four main themes subsumed 23 sub-themes. Heading the list were those under the general theme, Nationalism and the Struggle for Freedom. They were Sovereignty with 11 songs and Popular Democracy and People Empowerment with nine songs. Next were Militarization and Police Brutality, Political Participation and Good Governance, Poverty, The Exploitation of the masses, and Involvement in the Struggle for Democracy with three songs each. Nationalist Economy, Personal/Romantic Relations, Socialism and Equality and Omnibus Issues that Women espouse followed with two songs each. The rest, Nationalist Education, Political Detainees, The Rights of Indigenous People, Peace, Nuclear Threat to the Environment, Children's Rights, The Artist in the Midst of Injustice, Involvement in the Struggle for Sovereignty, The Plight of Teachers, The Plight of Overseas Workers, Prostitution, and Sexual Harassment and Rape, were represented by one song only. The results and findings reveal that Inang Laya's recorded social realist songs, with the corresponding issues and realities they articulate, do not only contribute to the promotion of a nationalist through years of struggle. This wise, songs serve as powerful communication tools, reflecting the inspirational, elucidating and watchdog functions of the media."